Ozbrojené konflikty na území bývalé Jugoslávie (Czech Journal of International Relations, 2000)
John B. Allcock, Marko Milivojevič, John J. Horton (eds.): Conflict in the Former Yugoslavia: AnEncyclopedia. ABC-CLIO, Denver; Santa Barbara, Oxford 1998, 440 stran, ISBN 0-87436-935-5 (hc),ISBN 1-57607-045-X (pbk).Tim Judah: Kosovo: War and Revenge. Yale University Press, New Haven, London 2000, 360 stran,ISBN 0-300-08313-0 (hbk), ISBN 0-300-08354-8 (pbk).